MicroRNAs in Kawasaki disease: An update on diagnosis, therapy and monitoring - Xiong, Yiyi; Xu, Jiawei; Zhang, Deju; Wu, Shuqin; Li, Zhangwang; Zhang, Jing; Xia, Zhongbin; Xia, Panpan; Xia, Cai; Tang, Xiaoyi; Liu, Xiao; Liu, Jianping; et al. (Frontiers in Immunology, 2022)
Kawasaki disease (KD) is an acute autoimmune vascular disease featured with long stage of febrile. It predominantly afflicts children under 5 years old and causes increased risk of cardiovascular combinations. The onset and progression of KD are impacted by many aspects, including genetic susceptibility, infection, and immunity. In recent years, many studies revealed that miRNAs, a novel class of small non-coding RNAs, may play a dispensable role in the development of KD via differential expression and participation in certain signaling pathways, such as the transforming growth factor-B(TGF-β) signaling pathway and the NF-κB signaling pathway. Accumulating clinical evidence indicated that miRNAs, as small molecular, could play the role of diagnostic biomarkers and exhibit extraordinary specificity and sensitivity. Besides, miRNAs have gained attention in affecting therapies for Kawasaki disease and providing new insights into personalized treatment. In this review, we systematically reviewed the existing literature and summarized those findings to analyze the latest mechanism to explore the role of miRNAs in the treatment of KD from basic and clinical aspects retrospectively. Our discussion helps to better understand the pathogenesis of KD and may offer profound inspirations on KD diagnosis, treatment, and prognosis.